Prakiraan Waktu Pelaksanaan Shutdown Maintenance di Kilang CDU V Balikpapan-Pertamina RU V - Ain Sahara; Adhi Susanto; Indah Susanti (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2012)
Refinery Crude Destilation Unit (CDU) V is part of the refinery. Distillation is a crude oil refinery processing crude oil into products which are often used in everyday life, such as gasoline, solar, kerosene, gas, and so. CDU is a distillation refinery process of crude oil by separating crude oil based on boiling points owned by each crude oil. The processing involves a wide range of controls and control instruments must have a reliable performance working process. The support of the implementation should be performed are often referred to the implementation of the shutdown maintenance within a specified period. In this study is the prediction time shutdown maintenance by using Reliasoft Software Weibull++ Version 7 with Weibull distribution function and linear regretion analysis. This using of this soft result of the most accurate rescheduling time to the implementation of the shutdown maintenance in revinery CDU V. The final result, shows that the shutdown maintenance should be done in once in 10 month. The result is expected to increase the optimal working performance of the tools of the company and finaly resulting the expected production outcome.